DETERMINATION OF LEAD (PB) CONTAMINATION IN LETTUCE (Lactuca sativa L.) FROM VARIOUS COLLECTION SOURCES IN BANDA ACEH, INDONESIA - Muhammad Afifi; Suprida Suprida; Agnia Purnama; Ruhul Maghfirah; Mutia Farida (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
Lettuce (Lactuca sativa L.) is a vegetable that is often consumed fresh, therefore the safety of its contents needs attention, especially regarding contamination with the heavy metal lead (Pb). This study aims to analyze Pb levels in lettuce obtained from the supermarket, traditional market, and local garden in Banda Aceh City using the Atomic Absorption Spectrophotometry method (AAS) and to evaluate differences in Pb content based on the source of acquisition. The analytical method was validated through linearity, sensitivity, and precision. The Pb calibration curve shows a good linear relationship with a coefficient of determination (R²) value of 0.9931. The limit of detection (LOD) and limit of quantification (LOQ) values were 0.162 mg/L and 0.492 mg/L, respectively. The precision test at low concentrations yielded a %RSD value of 4.91%, which met the method validation criteria. The results of the analysis showed that the Pb content in lettuce from the supermarket, traditional market, and local garden was 2.54 ± 0.12 mg/kg, 2.60 ± 0.07 mg/kg, and 2.38 ± 0.08 mg/kg, respectively, all of which exceeded the maximum Pb contamination limit according to BPOM (0.2 mg/kg). The one-way ANOVA test showed that there was no statistically significant difference (p > 0.05) between Pb levels among the different sources.